Water : What Can You Do? - Murphy, Glenn, 1908- (Australia Five Mile Press, 2009)
"Answers all your water questions and shows how you can take practical, positive steps to bring about change in the world." -- Back cover.
Include Index, Glossary and Illustration
Keywords: Water--Pollution -- Water conservation -- Water-supply